Review of the Odontesthes perugiae species group from Río de La Plata drainage, with the description of a new species (Atherinomorpha: Atherinopsidae) - Wingert, Juliana M.; Ferrer, Juliano; Malabarba, Luiz R. (Zootaxa, 2017)
Specimens presently identified as belonging to Odontesthes perugiae species group from rio Paraná, rio Uruguay and rio Negro in Argentina, Brazil and Uruguay are revised. Two species are recognized: Odontesthes perugiae, type species of the genus with Odontesthes orientalis as a junior synonym, and a new species described herein. Odontesthes perugiae is redescribed and its distribution restricted to the lower rio Paraná, lower rio Uruguay and rio Negro basins. The new species is endemic from the upper rio Uruguay above Salto do Yucumã (Brazil) or Saltos del Moconá (Argentina) falls. Both species share with the remaining taxa included in the O. perugiae species-group (O. bicudo, O. ledae, O. mirinensis, and O. piquava) the possession of teeth of the outer row on dentary and premaxilla shorter than those in the inner row, being distinguished from them by the number of gill rakers, body measurements and some osteological characters.